The Interaction Between Teacher Performance in Learning Implementation and Student Readiness on Social Science Learning Outcomes - Nurdin Nurdin; Imam Suseno; Ari Wahyu; Albertus Marua Setyastanto; Rinovian Rais (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores the interaction between teacher performance in conducting classroom learning and student readiness in relation to social science learning outcomes. A quantitative approach with a survey method was employed to collect data from senior high school students through structured questionnaires. The analysis reveals that both teacher performance and student readiness have a significant influence on student achievement when assessed individually. When considered simultaneously, the relationship remains statistically significant, although not particularly strong. These findings suggest that while teacher effectiveness and student preparedness are essential elements, other unexamined factors may also contribute to learning outcomes. The study underscores the importance of enhancing teacher competency through professional development and fostering student readiness through supportive learning environments. Such efforts are expected to create more meaningful and effective learning experiences that support academic success in the context of social science education.